High Resolution AFM and Single-Cell Resonance Raman Spectroscopy of Geobacter sulfurreducens Biofilms Early in Growth - Lebedev, Nikolai; Strycharz-Glaven, Sarah M.; Tender, Leonard M. (Frontiers in Energy Research, 2014)
AFM and confocal resonance Raman microscopy (CRRM) of single-cells were used to study the transition of anode-grown Geobacter sulfurreducens biofilms from lag phase (initial period of low current) to exponential phase (subsequent period of rapidly increasing current). Results reveal that lag phase biofilms consist of lone cells and tightly packed single-cell thick clusters crisscrossed with extracellular linear structures that appear to be comprised of nodules approximately 20 nm in diameter aligned end to end. By early exponential phase cell clusters expand laterally and a second layer of closely packed cells begins to form on top of the first. Abundance of c-type cytochromes (c-Cyt) is > 3-fold greater in 2-cell thick regions than in 1-cell thick regions. The results indicate that early biofilm growth involves two transformations. The first is from lone cells to 2-dimensionally associated cells during lag phase when current remains low. This is accompanied by formation of extracellular linear structures. The second is from 2- to 3-dimensionally associated cells during early exponential phase when current begins to increases rapidly. This is accompanied by a dramatic increase in c-Cyt abundance.